Antioxidant Activity Test of Ethanol and Water Extracts of Celery (Apium graveolens L.) - Nurmiati Nurmiati; Siti Nuryanti; Tahril Tahril (Jurnal Akademika Kimia, 2020)
This study aimed to determine the antioxidant activity of ethanol and water extracts of celery (Apium graveolens L.). Antioxidant activity test in this study used DPPH (2,2-diphenyl-1-picrylhydrazine) as a source of free radicals and vitamin C as a positive control. The antioxidant activity of celery extracts was analyzed using a UV-VIS spectrophotometer. Celery powder was extracted by firstly the maceration method using different solvents (ethanol and water) and secondly with the decoction method using water solvents. Celery extract was tested for antioxidant activity with various concentrations of 20, 40, 60, and 80 ppm. The results obtained that water extract (maceration) had a very strong antioxidant power with 23.713 ppm of IC50 values, for ethanol extract (maceration) had a strong antioxidant power with 59.492 ppm of IC50 value, water extract (dekok) had also a very strong antioxidant with 77.446 ppm of IC50 value, and vitamin C had a very strong antioxidant power with 15.631 ppm of an IC50 value. Based on the IC50 value obtained, the water extract by the maceration method was very good to be used as a source of natural antioxidants, because it had a very strong antioxidant activity value which was equivalent to vitamin C.